Availability of Pap Tests and Mammography in the Podkarpacie Province Provided Within the Framework of Population-Based Breast and Cervical Cancer Screening - Borowiec- Domka, Elżbieta; Barnaś, Edyta (European Journal of Clinical and Experimental Medicine, 2014)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Population-based programs of early detection of cervical and breast cancer that have been operating in Poland since 2006 are aimed at reducing morbidity and mortality from cervical and breast cancer. However, a decrease in morbidity recorded for a few years is too low. It results among others from low rates of target population coverage in both screening tests. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim of the study. Evaluation of the availability of Pap tests and mammography provided within the framework of prevention programs and to show how changes in the availability influenced attendance and cancer detection in the Podkarpacie Province. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Materials and methods. For the analysis the SIMP (System of Information Monitoring in Prophylaxis) data were used. Microsoft Excel 2010 and Statistica 10.1 were used to conduct the tests. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The number of providers in the Podkarpacie Province participating in preventive programs increased in the analyzed period (2007–2012) the most dynamic growth was observed in 2008. The increase in the number of providers in screening for breast cancer was accompanied with the increase in attendance in the period considered. However, the correlation between the attendance of women for the Pap test and the number of providers indicated a negative trend - the increase of providers was accompanied with the decrease in attendance in screening tests. The analysis showed that the number of detected cases of cervical cancers both for Poland and the Podkarpacie Province remained at a similar level in 2007–2011 with a slight downward trend. There is a similar tendency for breast cancer, however, the increase detected cases is more significant for Poland as compared to the Podkarpacie Province. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. The incidence of breast cancer increased in Poland, but to a lesser degree in the Podkarpacie Province. However, the number of cases of cervical cancer both in Poland and the Podkarpacie Province showed a downward tendency. The increase in the number of providers in both programs had a positive impact only on the increase in attendance in mammography in the Podkarpacie Province.